2003
DOI: 10.1001/jama.290.3.337
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Brain Overgrowth in the First Year of Life in Autism

Abstract: Context Autism most commonly appears by 2 to 3 years of life, at which time the brain is already abnormally large. This raises the possibility that brain overgrowth begins much earlier, perhaps before the first clinically noticeable behavioral symptoms. Objectives To determine whether pathological brain overgrowth precedes the first clinical signs of autism spectrum disorder (ASD) and whether the rate of overgrowth during the first year is related to neuroanatomical and clinical outcome in early childhood. Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

47
722
9
27

Year Published

2004
2004
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 981 publications
(818 citation statements)
references
References 48 publications
47
722
9
27
Order By: Relevance
“…These results suggest that forebrain neonatal 5-HT depletion causes permanent morphologic changes in the structure of the cerebral cortex, and these developmental alterations are evident within one week of serotonergic manipulation, at PND 7. This age in mouse is similar, in terms of cortical maturation, to the youngest children with autism who have increased cortical volumes [36][37][38]111].…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…These results suggest that forebrain neonatal 5-HT depletion causes permanent morphologic changes in the structure of the cerebral cortex, and these developmental alterations are evident within one week of serotonergic manipulation, at PND 7. This age in mouse is similar, in terms of cortical maturation, to the youngest children with autism who have increased cortical volumes [36][37][38]111].…”
Section: Discussionmentioning
confidence: 54%
“…-stereotypical behaviors, impaired verbal and nonverbal communication and blunted social interaction) are accompanied by structural and functional changes in cortex, cerebellum and amygdala [3,4,7,8,[19][20][21][22]37,38,49,55,67,101,125]. Structural and functional changes apparent in early childhood suggest that autism is a disorder of brain development [4,19,20,[37][38][39]111].…”
Section: Introductionmentioning
confidence: 99%
“…Since autism in an early developmental disorder, molecules that affect cell growth can be possible sites of biological defects. Courchesne et al [2003] have recently shown that autistic children have abnormal growth of the brain in the first year of life.…”
Section: Resultsmentioning
confidence: 99%
“…Neuroanatomical observations, along with data from functional magnetic resonance imaging, have shown that a major pathological hallmark in autistic individuals may be a premature brain overgrowth affecting structures such as the cerebral cortex, the limbic system, including the hippocampal formation and the amygdala, and the cerebellum (Courchesne et al, 2001(Courchesne et al, , 2003Sparks et al, 2002;Schumann et al, 2004). Such overgrowth would happen early before clinical diagnosis is made consistent with the possibility that growth factors, which normally regulate cell differentiation, proliferation and survival, having a functional role in the disease.…”
Section: Wnt Signaling and Autismmentioning
confidence: 93%